Mapping sites of gibberellin biosynthesis in the Arabidopsis root tip - Barker, Richard; Fernandez Garcia, Maria Nieves; Powers, Stephen J; Vaughan, Simon; Bennett, Malcolm J; Phillips, Andrew L; Thomas, Stephen G; Hedden, Peter (The New phytologist, 2021)
Root elongation depends on the action of the gibberellin (GA) growth hormones, which promote cell production in the root meristem and cell expansion in the elongation zone. Sites of GA biosynthesis in the roots of 7-d-old Arabidopsis thaliana seedlings were investigated using tissue-specific GA inactivation in wild-type (Col-0) or rescue of GA-deficient dwarf mutants. Tissue-specific GA depletion was achieved by ectopic expression of the GA-inactivating enzyme AtGA2ox2, which is specific for C19 -GAs, and AtGA2ox7, which acts on C20 -GA precursors. In addition, tissue-specific rescue of ga20ox triple and ga3ox double mutants was shown. Furthermore, GUS reporter lines for major GA20ox, GA3ox and GA2ox genes were used to observe their expression domains in the root. The effects of expressing these constructs on the lengths of the root apical meristem and cortical cells in the elongation zone confirmed that roots are autonomous for GA biosynthesis, which occurs in multiple tissues, with the endodermis a major site of synthesis. The results are consistent with the early stages of GA biosynthesis within the root occurring in the meristematic region and indicate that the penultimate step of GA biosynthesis, GA 20-oxidation, is required in both the meristem and elongation zone.
Keywords: regulace genové exprese u rostlin; proteiny huseníčku; gibberellin metabolism; root apical meristem; tissue-specific gibberellin depletion; Meristem; Arabidopsis Proteins; gibereliny; gibberellin action; tissue-specific mutant rescue; root elongation zone; meristém; Gene Expression Regulation, Plant; Arabidopsis; Gibberellins